2018
DOI: 10.1111/joop.12241
|View full text |Cite
|
Sign up to set email alerts
|

Is the validity of conscientiousness stable across time? Testing the role of trait bandwidth

Abstract: Although research into issues of conscientiousness bandwidth for personnel selection has compared global vs. facet validities using cross‐sectional designs, there has been an absence of longitudinal research. We provided the first empirical test of differential dynamicity between conscientiousness and its four facets across time, observing evidence suggesting dynamicity only for facets. Practitioner points We evaluated global and facet conscientiousness validities across four annual criterion measurement occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Furthermore, we found no clear evidence for increasing validities of APT over the 3‐year study program, besides small (descriptive) changes in the predictive validity of antisocial and obsessive‐compulsive tendencies with regard to GPA across the Bachelor program. Therefore, our results seem more in line with recent findings on the changeability of the validities of global compared to specific traits (Harari, Naemi, & Viswesvaran, ). Our results suggest that APT predict success throughout an (undergraduate) engineering study program in terms of “getting ahead” (e.g., obsessive‐compulsive), as well as “getting along” (e.g., antisocial) (Hogan & Holland, ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, we found no clear evidence for increasing validities of APT over the 3‐year study program, besides small (descriptive) changes in the predictive validity of antisocial and obsessive‐compulsive tendencies with regard to GPA across the Bachelor program. Therefore, our results seem more in line with recent findings on the changeability of the validities of global compared to specific traits (Harari, Naemi, & Viswesvaran, ). Our results suggest that APT predict success throughout an (undergraduate) engineering study program in terms of “getting ahead” (e.g., obsessive‐compulsive), as well as “getting along” (e.g., antisocial) (Hogan & Holland, ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding can be partially related to the bandwidth-fidelity debate in psychological assessment (Cronbach, 1990; Salgado, 2017). Some studies in personality and cognitive assessment have shown that bandwidth instruments have larger reliability and larger criterion-oriented validity than narrower measures (Ree et al, 1994; Salgado et al, 2013, 2015b; Salgado, 2017; Harari et al, 2019). This seems to be the case in the dimensions examined in this reliability generalization study, as the narrower dimensions (task, contextual, and positive performance) showed smaller interrater reliability than overall job performance.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of theory testing, Feeney et al (2015) tested anxiety coping theory by examining mean-level differences in applicant reactions. Similarly, Harari et al (2019) used SE tests to show that while global conscientiousness was consistently associated with performance outcomes, relationships with the facets of this trait varied over time. Their results suggested that researchers and practitioners should develop selection systems around broad traits that will be more generalizable over time (such as global conscientiousness).…”
Section: Using Me and Se To Advance Theory: A Taxonomy Of Mne Sourcesmentioning
confidence: 99%